Made in New York : 25 innovators who shaped our world - Vizard, Frank (Excelsior Editions, an imprint of State University of New York Press, 2023)
"When singer Frank Sinatra famously crooned about how if you can make it in New York, you can make it anywhere, he neglected to mention the things invented in New York travelled across the globe. New York has been a hotbed of life-changing innovation since its inception. MADE IN NEW YORK tells the stories behind the innovators and their inventions that are particularly relevant today. Like many New Yorkers, some came from elsewhere to find success in their new home. New Yorkers are no strangers to adversity and likewise many faced adversity due to racism and sexism. Some became famous; others struggled for recognition. All were visionaries and risk-takers who were willing to put their lives on the line if necessary. From the first brassiere to the life-saving pacemaker, from a solar lantern to the first mass-produced cameras, New York has been the seedbed of life-changing technologies that have altered how we live."-- Provided by publisher.
Keywords: Inventions -- New York (State) -- History.; Inventors -- New York (State) -- Biography.; Inventors -- New York (State) -- New York -- Biography.; New York (N.Y.) -- Civilization -- Miscellanea.; New York (State) -- Civilization -- Miscellanea.; Inventions -- New York (État) -- Histoire.; Inventeurs -- New York (État) -- Biographies.; Inventeurs -- New York (État) -- New York -- Biographies.; New York (État) -- Civilisation -- Miscellanées.; Middle Atlantic (DC.; Science & Technology.; BIOGRAPHY & AUTOBIOGRAPHY.; History.; TECHNOLOGY & ENGINEERING.; Inventions.; State & Local.; United States.; HISTORY.; Civilization; Inventions; Inventors; New York (State); New York (State) -- New York; Electronic books.; Biographies; History; Trivia and miscellanea; Biographies.